PELANGGARAN ETIKA DALAM BUMN: STUDI KASUS MEGA KORUPSI PT ASURANSI JIWASRAYA - Austin Hotdo Sagala; Fadillah Nuryanti; Kayla Issaura Maritza Adryenne; Rindu Ayu Dyah Pasha Sulasmi (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Corruption involving state-owned companies not only harms state finances but also tarnishes the integrity of the government's business sector. This study reveals in detail various aspects of ethical violations that occurred in the management and operations of PT Asuransi Jiwasraya, providing in-depth insight into the social and economic impacts of these acts of corruption. The implications for the reputation of BUMN and steps that can be taken to improve corporate governance to be more ethical are also detailed in this journal. The purpose of this writing is to analyze the importance of the role of ethics in the profession, especially in the government sector. The method used in this research is a normative juridical method. The results of the analysis provide the fact that OJK supervision is not effective in the insurance industry, which is detrimental to many parties.